Factors related to top running speed and economy - Nummela, A.; Keränen, T.; Mikkelsson, L. O. (International Journal of Sports Medicine, 2007)
The main purpose of the present study was to investigate the relationships between running mechanics, top running speed and economy in young endurance athletes. Twenty five endurance athletes (age 19.8 ± 1.1 years, stature 1.82 ± 0.07 m and body mass 69.4 ± 7.5 kg) performed two separate tests on an indoor track. The first test was 8 × 30 m with increasing speed, and the second test was incremental 5 - 6 × 1000 m. In the first test, ground reaction forces and stride characteristics were measured from each running speed. In the second test, running economy at the speed of 3.89 m · s-1 and maximal oxygen uptake were determined. Ground contact time was the only factor which correlated significantly with both running economy (r = 0.49, p < 0.05) and maximal running speed (r = - 0.52, p < 0.01). Furthermore, maximal running speed was correlated significantly with the mass-specific horizontal force (r = 0.56, p < 0.01) but not with the vertical effective force. It is concluded that the short contact times required in economical and high speed running suggests that fast force production is important for both economical running and high top running speed in distance runners.